Association between false-positive TORCH and antiphospholipid antibodies in healthy pregnant women. (April 2018) - De Carolis, S; Tabacco, S; Rizzo, F; Perrone, G; Garufi, C; Botta, A; Salvi, S; Benedetti Panici, P; Lanzone, A
The present study investigated: (a) the presence of antiphospholipid antibodies and (b) the obstetric outcome in healthy pregnant women showing false-positive TORCH—Toxoplasmosis, Other: syphilis, varicella-zoster, Rubella, Cytomegalovirus (CMV), and Herpes infections—results. Data from 23 singleton healthy pregnancies with false-positive TORCH results were collected. Each woman was systematically screened for TORCH IgG and IgM during the pre-conception assessment and/or at the beginning of pregnancy. In the presence of IgM positivity, when indicated (CMV, toxoplasmosis, rubella, herpes simplex virus), IgG avidity was evaluated and, if possible, polymerase chain reaction was performed on an amniotic fluid sample in order to distinguish between primary infection or false positivity. The antiphospholipid antibodies tests were: lupus anticoagulant, anticardiolipin antibodies IgG, IgM, and anti-β2glicoprotein I IgG, IgM. The antiphospholipid antibodies tests, if positive, were repeated after 12 weeks to confirm the results. In pregnant women with false-positive TORCH, the overall prevalence of positive antiphospholipid antibodies for one or more tests was 52.2%. To clarify the correlation of false-positive TORCH results with clinical practice, obstetric outcome was analyzed in terms of live births, week of delivery, neonatal birth weight, and neonatal birth weight percentile. A statistically significant lower neonatal birth weight and neonatal birth weight percentile were observed in women with false-positive TORCH associated with antiphospholipid antibodies positivity (Group A) in comparison with those in women with false-positive TORCH without antiphospholipid antibodies positivity (Group B). No statistically significant difference was found for the week of delivery between the two groups. It is hoped that future studies will verify the life-long persistence of antiphospholipid antibodies positivity by follow-up of these women and identify who will develop a classical antiphospholipid syndrome or other autoimmune disorders.